Primer registro de Taxidea Taxus Berlandieri Baird, 1858 (Mammalia: Carnivora: Mustelidae) para el estado de Veracruz, México - González-Christen, A.; González-Romero, A.; Rodríguez-Colmenares, J. S. (Instituto de Ecología, A.C., 2006)
Examines the first record of the badger in the state of Veracruz in 1858 by Baird. The nearest known locality for this species outside of Veracruz is the state of Puebla, 80 kilometres in a straight line southwest. Standard and skull morphometric measures of the specimen are included, as well as data about the animal’s habitat. The badger is protected in Mexico as an endangered species under the NOM-059-SEMARNAT-2001.